Theology and Practice verses text: The lord’s supper in Acts 2 - David B Presley (Sekolah Tinggi Teologi Jemaat Kristus Indonesia, Salatiga, 2022)
The influence of theology and practice on interpretation is discussed and applied to communion practices. These practices are considered with specific attention to Acts chapter 2. The paper will focus on the frequency of observing the Lord’s Supper as presented in Acts. A prior commitment to traditional practices and theologies can lead to conclusions that are at odds with what is found there. Attention will be given to practices within the Churches of Christ and Christian Churches in America and how their theology and practices impact their understanding of Acts 2. The two apostolic precedents in Acts (2:46; 20:7) are proposed as guides to celebrating the Lord’s Supper on Sunday and other occasions that do not fall on the first day of the week. Several examples are given to illustrate how these precedents and principles would be applied.Keywords : Theology, Lord’s Supper, Acts 2